LEAN Management Models Application and Safety Management of Logistics Firm in Nigeria - Adebiyi, Sulaimon Olanrewaju; Bassey, Queen E.; Amole, Bilqis B. (Applied Studies in Agribusiness and Commerce, 2022)
The need for lean concepts application in the safety management of logistics processes cannot be emphasized as it can help in enhancing the flow of information and expediting processes within the supply network for improved organizational outcomes. The study investigated the application of lean management models to the safety management of logistics firms in Nigeria. The study population includes 215 employees of Manal Plant hire Ltd Nigeria. 138 employees were chosen using a purposive sampling method. A self-administered questionnaire was designed to collect the primary data from the respondents. The data collected were analyzed using the structural equation modeling (SEM) technique to test the hypotheses developed in the study. The study’s findings suggest that Process and Equipment Management has a positive and significant effect on the operational efficiency and workplace safety of the studied firms; employee empowerment has a positive and significant effect on operational efficiency; technological innovation has a positive and significant effect on the operational efficiency, and that continuous improvement has a positive and significant effect on the operational efficiency and workplace safety. It is, therefore, concluded that the adoption of Lean Management has a positive and significant effect on the safety management of logistics firms. The study recommends that manufacturing, logistics, and service industries should be committed to carrying out process mapping to eliminate non-value-adding operations in production as well as logistics and ensure the effective and continuous flow of logistics operations.